1981
DOI: 10.1111/j.1469-1809.1981.tb00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin heavy chain genes in humans are located on chromosome 14

Abstract: The human immunoglobulin heavy chain gene complex has been assigned to chromosome 14 by filter hybridization of restriction digests of mouse-human somatic cell hybrids. Cloned DNA probes for both variable and constant regions were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(22 citation statements)
references
References 18 publications
(11 reference statements)
0
21
0
1
Order By: Relevance
“…For lymphoid tumours, one of the ®rst clues came from the mapping of the human immunoglobulin (Ig) heavy chain locus to the long arm of chromosome 14 (Croce et al, 1979;Hobart et al, 1981). At the time, gene mapping by chromosome in situ hybridization was restricted to multi-copy genes but we used the technique to map the human K light chain genes to chromosome 2, band p12 (Malcolm et al, 1982), using a variable region probe (which is e ectively multi-copy due to cross hybridization between di erent V genes (Bentley and Rabbitts, 1981)).…”
Section: Cloning Genes At Chromosomal Translocation Breakpointsmentioning
confidence: 99%
“…For lymphoid tumours, one of the ®rst clues came from the mapping of the human immunoglobulin (Ig) heavy chain locus to the long arm of chromosome 14 (Croce et al, 1979;Hobart et al, 1981). At the time, gene mapping by chromosome in situ hybridization was restricted to multi-copy genes but we used the technique to map the human K light chain genes to chromosome 2, band p12 (Malcolm et al, 1982), using a variable region probe (which is e ectively multi-copy due to cross hybridization between di erent V genes (Bentley and Rabbitts, 1981)).…”
Section: Cloning Genes At Chromosomal Translocation Breakpointsmentioning
confidence: 99%
“…A principle example of this is the translocation t(8;14)(q24;q32.1) invariably found in the human B cell tumor Burkitt's lymphoma (Manolov and Manolov 1972;Zech et al 1976). The link with the immunoglobulin H-chain locus on chromosome 14, band q32.1 (Croce et al 1979;Hobart et al 1981) and subsequently with the K light-chain locus on chromosome 2, band p12 (Malcolm et al 1982), suggested that the immunoglobulin genes might be associated with the translocation breakpoints. The cloning of the CMYC proto-oncogene associated with the IgH locus from Burkitt's lymphoma translocation breakpoint t(8;14)(q24;q32) confirmed this.…”
mentioning
confidence: 99%
“…The VH genes have been localized to chromosome 14 by somatic cell hybrids (23) and several have been cloned and sequenced. Matthyssens and Rabbitts (24) found several instances in which two Ig VHIII genes were found within a single phage, separated by 12-16 kilobases (kb) of spacer DNA (25).…”
mentioning
confidence: 99%
“…We next wanted to test for linkage between the VH polymorphic loci and the CH loci also present on chromosome 14 in humans (23). All of the informative families for VH region loci had been typed previously for CH region markers and all were informative at the latter locus for testing linkage between the two clusters.…”
mentioning
confidence: 99%